P10 High troponin I in acute liver failure: a marker of myocardial injury or metabolic stress?. (16th November 2010) - Audimoolam, V; Wendon, J; Bernal, W; Willars, C; Mcphail, M; Auzinger, G
Abstract : Introduction: ALF is a life-threatening multi-system illness resulting from massive hepatic necrosis. Acute liver failure (ALF), in its more severe forms is invariably complicated by progressive haemodynamic disturbances with a pattern of distributive shock; elevated cardiac output and decreased peripheral vascular resistance being the standard apart from hypoxic hepatitis of cardiac origin. A recent study demonstrated a relatively high incidence of elevated troponin I (TI) in patients presenting with ALF; elevated levels were associated with poorer outcome attributed to myocardial damage. Data pertaining to invasive haemodynamic monitoring or cardiac imaging studies have not been described in conjunction with TI measurement. Method: We prospectively collected invasive haemodynamic data (transpulmonary thermodilution cardiac output measurements PICCO) and echocardiographic studies in a cohort of patients with ALF. These data were analysed along with TI levels, taken routinely on admission to a tertiary liver centre. TI levels were considered positive if >0.05 μg/l or "high" if over the 50th centile. Results: A total of 191 patients who fulfilled criteria for ALF and subacute liver failure (ALF/SALF) were enrolled from 2007 to 2010. 121 patients had an elevated T I > 0.05 μg/l on admission (102/19-ALF/SALF, p=0.128 χ 2 test). 122 patients underwent echocardiogram; 50 of the TI negative group (TI-neg) and 72 in the TI positive group (TI-pos); p<0.001 χ 2 test. Median TI levels was 0.075 μg/L (0–8.52) in those who survived and 0.180 μg/l (0–50) in those who either died or were transplanted; p=0.051, Mann–Whitney U test. There was no statistically significant association identified in regard of regional wall motion abnormalities between TI pos/ neg groups (7/78 vs 1/36, p=0.461 χ 2 test) or TI high (>0.7) or low groups (<0.21) (6/66 vs 2/48; p=0.563 χ 2 test). A borderline association was noted between TI pos and left ventricular dysfunction (LVD) (15/70 vs 1/36, p=0.050, χ 2 test), LVD was seen in (22%) high TI vs (6%) in the low TI group. No difference in haemodynamic parameters were noted between the TI neg and pos groups for MAP (70 (50–124) vs 70 (45–180); p=0.221), Cardiac index (4.45 (3.0–6.9) vs 4.5 (2.0–7.67); p=0.336) Blood volume-ITBVI (720 (488–1186) vs 783 (426–1392); p=0.207) Lung water-EVLWI (9 (6–18) vs 9 (5–34); p=0.998; all Mann–Whitney U test). Subjects with elevated TI had an elevated median creatinine kinase (CK) (329 (6–37840) IU/L vs 81 (14–1417) IU/L (p=<0.001, Mann–Whitney U test). Elevated CK in this cohort may not be representative of cardiac damage as elevated levels secondary to rhabdomyolysis were often seen in patients presenting with recreational drug use. Conclusion: Troponin I elevation observed in ALF/SALF may not represent true myocardial injury and may be better viewed as a marker of metabolic stress. TI is not associated with directly measured haemodynamic abnormalities in ALF patients. Novel serum markers are needed to better reflect cardiovascular compromise in ALF.